2022
DOI: 10.1088/1748-9326/ac94e9
|View full text |Cite
|
Sign up to set email alerts
|

Strong trade-offs characterise water-energy-food related sustainable development goals in the Ganges–Brahmaputra–Meghna River basin

Abstract: The United Nations’ Sustainable Development Goals (SDGs) set ambitious policy targets for 2030 to overcome poverty while preserving the planet. These goals are not perfectly aligned; trade-offs emerge during implementation at regional and local levels, such as in a river basin. Here, we quantify important trade-offs between water, energy, and food-related SDGs in the Ganges-Brahmaputra-Meghna River basin, a climate vulnerability hotspot, using multi-objective optimisation based on detailed water resources and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In India's cereal producing regions, policy scenario development showed that energy pricing tools could reduce agricultural demand for water with minimal impacts on production, resulting in the same outcomes as water withdrawal quotas by the year 2050 (Singh et al 2023). However, in the stressed Ganges-Brahmaputra-Meghna river basin, emphasizing sustainable development goals related to agricultural profitability over those related to food production goals would reduce the number of people fed by an estimated two-thirds (Siderius et al 2022).…”
Section: Governance and Policy For Water-limited Agricultural Regionsmentioning
confidence: 99%
“…In India's cereal producing regions, policy scenario development showed that energy pricing tools could reduce agricultural demand for water with minimal impacts on production, resulting in the same outcomes as water withdrawal quotas by the year 2050 (Singh et al 2023). However, in the stressed Ganges-Brahmaputra-Meghna river basin, emphasizing sustainable development goals related to agricultural profitability over those related to food production goals would reduce the number of people fed by an estimated two-thirds (Siderius et al 2022).…”
Section: Governance and Policy For Water-limited Agricultural Regionsmentioning
confidence: 99%
“…However, most existing studies have failed to consider carbon emissions from food production and the effects of agroecosystem carbon sinks on the allocation of water and land resources. Under the premise of considering carbon emissions, researchers have begun to search for optimal water and land resource allocation strategies for sustainable agricultural development from a water-energy-foodcarbon nexus perspective, i.e., in the Yellow River Basin [84] and on the Indo-Gangetic Plain [75,153]. An agricultural high-quality development program is committed not only to achieving high resource utilization efficiency and economic benefits but also to achieving low-carbon emissions and a low risk to human health.…”
Section: Wlfc Collaborative Management In Large Global River Basinsmentioning
confidence: 99%
“…Our approach can moreover be applied for other regions where water and food security strongly interlink with climatic and socioeconomic changes. Contextually similar complex river basins where irrigation plays a strong role, such as the Nile, Ganges and Mekong (Johnston & Smakhtin, 2014;Siderius et al, 2022), may be of particular interest.…”
Section: Benefits Of Spatial and Multi-objective Pathways For Adaptat...mentioning
confidence: 99%